Whose pharaohs? : archaeology, museums, and Egyptian national identity from Napoleon to World War I - Reid, Donald M. (Donald Malcolm), 1940- (University of California Press, 2002)
Egypt's rich and celebrated ancient past has served many causes throughout history--in both Egypt and the West. Concentrating on the era from Napoleon's conquest and the discovery of the Rosetta Stone to the outbreak of World War I, this book examines the evolution of Egyptian archaeology in the context of Western imperialism and nascent Egyptian nationalism. Traditionally, histories of Egyptian archaeology have celebrated Western discoverers such as Champollion, Mariette, Maspero, and Petrie, while slighting Rifaa al-Tahtawi, Ahmad Kamal, and other Egyptians. This exceptionally well-illustrated and well-researched book writes Egyptians into the history of archaeology and museums in their own country and shows how changing perceptions of the past helped shape ideas of modern national identity. Drawing from rich archival sources in Egypt, the United Kingdom, and France, and from little-known Arabic publications, Reid discusses previously neglected topics in both scholarly Egyptology and the popular "Egyptomania" displayed in world's fairs and Orientalist painting and photography. He also examines the link between archaeology and the rise of the modern tourist industry. This richly detailed narrative discusses not only Western and Egyptian perceptions of pharaonic history and archaeology but also perceptions of Egypt's Greco-Roman, Coptic, and Islamic eras. Throughout this book, Reid demonstrates how the emergence of archaeology affected the interests and self-perceptions of modern Egyptians. In addition to uncovering a wealth of significant new material on the history of archaeology and museums in Egypt, Reid provides a fascinating window on questions of cultural heritage--how it is perceived, constructed, claimed, and contested